Role of the USP7/FOXO3A axis in environmentally relevant doses of arsenic-induced lung carcinogenesis: Insights from bioinformatics analysis and model of human epithelial cell malignant transformation - Xiaoyu Chen; Yuqing Wang; Ziqi Liu; Yujie He; Huan Gao; Xinchao Guan; Liping Chen; Shen Chen; Xiumei Xing; Wen Chen; Daochuan Li; Qing Wang (Ecotoxicology and Environmental Safety)
Arsenic (As) is classified as a Group 1 carcinogen by the International Agency for Research on Cancer (IARC). Exposure to As has been associated with an increased risk of various cancers, particularly lung cancer. However, the precise molecular mechanisms contributing to this carcinogenesis are not well understood. In our study, we analyzed transcriptomic data from the GEO database (GSE36684), identifying 764 differentially expressed genes (DEGs) in BEAS-2B cells treated with environmentally relevant doses of As for 8 weeks. A KEGG pathway enrichment analysis suggested that the FoxO pathway activation might be a novel key signaling event in As-induced carcinogenesis. We further analyzed the expression of 11 DEGs involved in the FoxO pathway using the TCGA-LUSC dataset. The findings revealed that four genes displayed expression patterns in tumor tissues consistent with those observed after As treatment in GEO dataset. Among them, USP7 was upregulated, while ATM, S1PR1, and PLK2 were downregulated in cancer tissues. High USP7 expression was specifically linked to a poor prognosis in lung squamous cell carcinoma (LUSC). To explore the role of USP7 in As-induced malignant transformation, BEAS-2B cells were exposed to NaAsO2 concentrations of 0.2 μM and 2 μM for up to 20 weeks. Experimental results confirmed that NaAsO2 treatment suppressed the FoxO transcriptional activity by upregulating USP7 expression, subsequently downregulating ATM and PLK2 expression, which led to abnormalities in cell cycle regulation and apoptosis. Notably, knocking down USP7 in As-transformed cells resulted in significant reductions in cell proliferation, colony formation, and tumor formation ability in nude mice, indicating the USP7-regulated FOXO3A pathway could be central to As-induced lung carcinogenesis. Moreover, our research demonstrated that USP7 inhibited FOXO3A’s ability to translocate from the cytoplasm to the nucleus by affecting its monoubiquitination status. Additionally, we speculated that As-induced the elevation of USP7 expression due to the excessive inflammatory cytokines secretion and the activation of mTORC1/WTAP pathway. These findings offer novel insights into the molecular mechanisms underlying As-mediated lung cancer.